Pengaruh Affiliate, Content Marketing Serta Brand Awareness di Social Commerce Terhadap Impulse Buying Masyarakat Surabaya - Andika Yuda Prasetya; Rusdi Hidayat Nugroho (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Industrial resolution is occurring due to the impact of globalization which is getting bigger every year which results in technological developments. With the increasingly rapid development of technology, it will have an impact on all aspects, especially the economy, such as the emergence of new phenomena such as social commerce which emerged after the existence of e-commerce as a shopping medium but became one in social media. And another phenomenon caused by technological developments is the emergence of the affiliate marketing profession, which is currently being discussed and is also being used as a new marketing strategy by companies. Affiliate marketing is believed to be able to promote goods/services very well. In this research the author used an associative quantitative approach. The sample used was the entire population, namely 102 respondents. The data collection technique used in this research was a questionnaire. The data analysis techniques used are validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression test, coefficient of determination test, as well as F test and T test, using SPSS 26. The results of the research on the F Test show that there is a very significant influence jointly between affiliate marketing, content marketing and brand awareness on increasing impulse buying. The results of the T Test research show that affiliate marketing, content marketing and brand awareness have a positive and significant effect on increasing impulse buying.